Abdominal Wall Reconstruction with Retrorectus Self-Adhering Mesh: A Single-Center Long-Term Follow-Up. Issue 3 (29th November 2022) - Bashian, Elizabeth; Daoud, Georges; Khansa, Ibrahim; Janis, Jeffrey E.
Abstract : Background: Mesh repair has been demonstrated to be superior to suture alone in ventral hernia repair. In a previous short-term pilot study, the authors found lower postoperative narcotic requirements with self-adhering mesh. The aim of this study was to follow-up on that pilot study, using long-term data. Methods: This is a retrospective review of a prospectively collected database. All patients who underwent ventral hernia repair with retrorectus mesh and who had at least a 12-month follow-up were reviewed. Comparisons were performed between patients who received self-adhering mesh and those who received transfascially sutured mesh, using matched-pair analysis, examining perioperative outcomes, surgical-site occurrences, and hernia recurrence/bulge. Results: Forty-two patients were included in the study, with 21 patients undergoing repair with transfascially sutured mesh and 21 patients receiving self-adhering mesh. Average length of follow-up was 1078 days. There were no significant differences between the two groups in baseline characteristics. Patients receiving self-adhering mesh had significantly shorter surgery, and a shorter hospital length of stay. They also had a tendency toward lower narcotic requirements. There were no significant differences in the rate of surgical-site occurrences, hernia recurrences, or bulge between the two groups. Conclusions: This long-term study shows that self-adhering mesh in ventral hernia repair results in similar long-term outcomes to transfascially sutured mesh, with shorter surgery, shorter length of stay, and a tendency toward improved pain control. These findings mirror the known advantages of self-adhering mesh in inguinal hernia repair. Further research is needed to study the incidence of chronic pain and the cost-effectiveness of self-adhering mesh. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.